Strategic market evaluation of Starbucks in Taiwan: A swot analysis of brand positioning, consumer adaptation, and growth opportunities in a tea-dominated culture - Ganbat, Enkhsolongo; Novak, Marko (Edelweiss Applied Science and Technology, 2025)
This study examines Starbucks’ strategic position in Taiwan using a qualitative SWOT analysis. The research evaluates Starbucks’ strengths, weaknesses, opportunities, and threats in the Taiwanese market. Key strengths include global brand recognition, the "Third Place" concept, and advanced digital engagement through the Starbucks mobile app. Major weaknesses involve premium pricing and limited localization of menu offerings. Opportunities lie in expanding into smaller cities, leveraging Taiwan’s growing coffee culture, and advancing sustainability initiatives. Threats encompass economic fluctuations, rising operational costs, and persistent cultural preferences for tea. While Starbucks enjoys a strong brand presence, adapting products and pricing strategies is essential for deeper market penetration and long-term competitiveness in Taiwan. The study suggests actionable strategies such as enhancing local menu innovation, expanding geographic reach, and strengthening sustainability practices to improve Starbucks’ market position and resilience against regional competition. Furthermore, this analysis fills a gap in current literature by focusing on Starbucks' strategic adaptation within Taiwan's unique beverage market, distinguishing itself from prior studies through its emphasis on localized product innovation and digital engagement tailored to Taiwanese consumer preferences.